2017
DOI: 10.1007/s12265-017-9733-5
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Bovine Pericardium-Based Tissue Biomaterial with Irreversible Chemistry Improves Biochemical and Biomechanical Properties

Abstract: Bioprosthetic heart valves (BHVs), derived from glutaraldehyde crosslinked (GLUT) porcine aortic valve leaflets or bovine pericardium (BP), are used to replace defective heart valves. However, valve failure can occur within 12–15 years due to calcification and/or progressive structural degeneration. We present a novel fabrication method that utilizes carbodiimide, neomycin trisulfate, and pentagalloyl glucose crosslinking chemistry (TRI) to better stabilize the extracellular matrix of BP. We demonstrate that T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 43 publications
5
67
0
5
Order By: Relevance
“…70,88 The aforementioned advantages of PGG have paved the path for its use in tissue engineering studies of valves, development of vascular grafts, and numerous other potential therapeutic applications. 32,33,35,39,47,88,119,120,129,154,156,167,168,170,171 In this review, we critically evaluate recent work relevant to drug-delivery and translation-related applications of PGG.…”
Section: Functionality Of Pentagalloyl Glucosementioning
confidence: 99%
“…70,88 The aforementioned advantages of PGG have paved the path for its use in tissue engineering studies of valves, development of vascular grafts, and numerous other potential therapeutic applications. 32,33,35,39,47,88,119,120,129,154,156,167,168,170,171 In this review, we critically evaluate recent work relevant to drug-delivery and translation-related applications of PGG.…”
Section: Functionality Of Pentagalloyl Glucosementioning
confidence: 99%
“…Little to no calcification was found on any of the leaflets. The study showed the potential benefits of using this cross-linking method to prevent or delay calcification in implants, though further data should be collected (Figure 3) [5]. Treating the biomaterial with POSS to form POSS-PCU changes existing receptors so that free calcium ions are no longer able to bind, preventing deposition and mineralization [5].…”
Section: Biomaterials Alterations and Coatingsmentioning
confidence: 99%
“…Several crosslinking methods, specifically crosslinking with glutaraldehyde, provide strength by preventing degradation, but the elastin in the ECM is not protected. This leads to stiffness, tears, and deformations in the surface of the material, a condition known as "permanent set" [5]. A modified form of crosslinking involving treating the surface of biomaterial implants with pentagalloyl glucose does not cause damage to collagen or surface deformations.…”
Section: Biomaterials Alterations and Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges in translating the data from pre-clinical and clinical pilot trials that will ultimately be faced by all tissue engineering projects are also reviewed [4]. The experimental studies in this issue address a variety of topics within the heart valve field including two papers on the development of decellularised valves [5,6], the chemical fixation of bovine pericardium and the assessment of a new transcatheter heart valve [7,8]. Within the vascular field, there are two papers, the first addresses the use of an in vivo approach that utilises the host reaction to an implanted biomaterial for the generation of completely autologous tissues, while the second examines the use of intravascular echo as a tool to evaluate the changes within tissue-engineered valves implanted into sheep [9,10].…”
mentioning
confidence: 99%